Pattern recognition in industry - Bhagat, Phiroz (Elsevier, 2005)
- "Find it hard to extract and utilise valuable knowledge from the ever-increasing data deluge?" If so, this book will help, as it explores pattern recognition technology and its concomitant role in extracting useful information to build technical and business models to gain competitive industrial advantage.- *Based on first-hand experience.